The Use of (PERT and CPM) Techniques to Analyze a Project Network (an Applied Study on Al-Mustafa Complex Construction Project in Al-Hartha District): The Use of (PERT and CPM) Techniques to Analyze a Project Network (an Applied Study on Al-Mustafa Complex Construction Project in Al-Hartha District) - Abbas, Duaa (The Gulf Economist, 2023)
As a result of the continuous development, the importance of operations research, especially business networks, has increased to manage various projects to ensure the utilization of time, effort and available capabilities. Time is an important factor in the completion of projects, it has become necessary to use modern scientific planning and scheduling methods, due to the presence of large and complex projects that include multiple and overlapping activities. The research aims to use the Critical Path Method (CPM) and the Program Evaluationand Review Technique (PERT) for the purpose of reaching the optimal time and the lowest cost and in light of the available capabilities.The study found out that without using the business network in Al- Mustafa Residm complex, it has negative impact on the period of project implementation as the Actual implementation period reached (1440) days. While using business networking techniques (CPM, PERT), it reached (1001). So there is a clear difference estimated at (440) days, as the project network data was analyzed by using the program (WinQSB).